PENGARUH KECERDASAN EMOSIONAL SISWA SMP TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIK DAN PEMECAHAN MASALAH - Reza Hapsyah; Neda Permana; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This research aims to know the influence of emotional intelligence against the ability of understanding and solving mathematical problems. This research was quasi experimental research which is done once a Junior High School in Cimahi with samples as many as 60 grade VII include the 30 students into A group of students and 30 other students to become students in Group b. Conclusion from this research is that emotional intelligence affect the ability of the students comprehension and problem solving mathematics in levels of being. Where emotional intelligence has no effect, however, many very influential if low students emotional intelligence